Cell numbers in the reflected blade of CA3 and their relation to other hippocampal principal cell populations across seven species - Jovana Maliković; Irmgard Amrein; Irmgard Amrein; Lorenzo Vinciguerra; Dušan Lalošević; David P. Wolfer; David P. Wolfer; Lutz Slomianka; Lutz Slomianka (Frontiers Media S.A., 2023)
The hippocampus of many mammals contains a histoarchitectural region that is not present in laboratory mice and rats-the reflected blade of the CA3 pyramidal cell layer. Pyramidal cells of the reflected blade do not extend dendrites into the hippocampal molecular layer, and recent evidence indicates that they, like the proximal CA3 pyramids in laboratory rats and mice, partially integrate functionally with the dentate circuitry in pattern separation. Quantitative assessments of phylogenetic or disease-related changes in the hippocampal structure and function treat the reflected blade heterogeneously. Depending on the ease with which it can be differentiated, it is either assigned to the dentate hilus or to the remainder of CA3. Here, we investigate the impact that the differential assignment of reflected blade neurons may have on the outcomes of quantitative comparisons. We find it to be massive. If reflected blade neurons are treated as a separate entity or pooled with dentate hilar cells, the quantitative makeup of hippocampal cell populations can differentiate between species in a taxonomically sensible way. Assigning reflected blade neurons to CA3 greatly diminishes the differentiating power of all hippocampal principal cell populations, which may point towards a quantitative hippocampal archetype. A heterogeneous assignment results in a differentiation pattern with little taxonomic semblance. The outcomes point towards the reflected blade as either a major potential player in hippocampal functional and structural differentiation or a region that may have cloaked that hippocampi are more similarly organized across species than generally believed.